Women Empowerment in India - A Perspective - Ankita Dey; Kunal K Majumdar; Arun Kumar Chakraborty; Asok Kumar Mandal (Medsci Publications, 2018)
Background: The study presents an index of women empower- ment based on a statistical technique of data reduction viz. factor analysis and provides an in depth analysis of states in India with respect to the National Family Health Survey-4 (NFHS-4) dataset. Methods: The dataset on several indicators of women well being are selected from the dataset obtained from the Open Government Data platform (ODG) India. The items are statistically grouped to form component indices and subsequently the aggregative index of women empowerment. Positions of states are analyzed accord- ing to the scale of indices. Relationships between the components are also measured using correlation analysis. Results: The factor analytic model identifies grouping in the data and also explains the variation among the indicators or the hetero- geneity among the population to a great extent (73%). Women empowerment is divided into six factors or groups namely knowl- edge & education, general health & social status, family planning, fertility & access to health care services, economic independence & decision making, violence against women and addiction. The scores attached to each of the components are evaluated and pre- sented for each state. Conclusions: The study explains the importance of women em- powerment in the light of the recently adopted sustainable devel- opment goals for 2030. The current scenario of Indian states in various socio economic, demographic and health indicators of well being of women will be useful in constructing strategies and plans regarding development.